Factors Influencing Psychological Well-Being of Covid-19 Survivors in Tembalang District Semarang City (Nursing Care Journal, 2023)
The Covid-19 pandemic has caused the emergence of social stigma that can provide inequality of access to Covid-19 survivors who are labeled negatively. This condition disrupts the psychological well-being of Covid-19 survivors. This study aims to determine the factors that influence the psychological well-being of Covid-19 survivors in Tembalang District, Semarang City. This study is a correlational analytical study with a cross-sectional approach . This study uses an accidental sampling technique . The number of samples in this study was 65 respondents. Based on the chi-square test , the results of the study showed that there was a relationship between gender and the psychological well-being of Covid-19 survivors in Tembalang District, Semarang City (p = 0.008), there was a relationship between age and the psychological well-being of Covid-19 survivors in Tembalang District, Semarang City (p = 0.003), there was a relationship between employment status and the psychological well-being of Covid-19 survivors in Tembalang District, Semarang City (p = 0.025), and there was a relationship between education level and the psychological well-being of Covid-19 survivors in Tembalang District, Semarang City (p = 0.046). Therefore, it is recommended for health centers in the Tembalang District area to be able to improve psychological well-being, one way is by providing guidance and counseling for Covid-19 survivors to be able to get through the trauma caused by Covid-19.